POTENSI SIRUP BUAH NAGA: ANALISIS KOMPARATIF KUALITAS SENSORI DAGING DAN KULIT BUAH - Rahma, Azizah Septia; Elida, Elida; Holinesti, Rahmi; Mustika, Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Dragon fruit (Hylocereus spp.) has great potential in food processing, but the use of fruit peels is still limited. This study aims to analyze the difference in the sensory quality of syrup made from the juice of the flesh and skin of red dragon fruit through a hedonic test approach. The research method used pure experiments with a completely random design involving 30 consumer panelists from the Family Welfare Education Study Program at Padang State University. Data collection was carried out through sensory tests using a 7-point hedonic scale to assess four parameters: color, aroma, texture, and taste. The results showed a significant difference only in the color parameter, with dragon fruit juice obtaining an average score of 6.01 compared to dragon fruit peel with 5.59 (t-count 3.172, p < 0.05). The aroma, texture, and taste parameters did not show significant differences, with very close average scores. Statistical analysis revealed that both types of syrup had relatively equivalent sensory qualities, with individual panelist variations ranging from 0.927-1.368. This research makes an important contribution to the exploration of the use of dragon fruit peels as an alternative raw material for food products, as well as encouraging innovations in sustainable agricultural waste processing.Keywords: Dragon Fruit, Syrup, Hedonic Test, Sensory Quality, Agricultural Waste.